Evaluation of Antioxidant, Thrombolytic and Cytotoxic Potentials of Methanolic Extract of Aporosa wallichii Hook.f. Leaves: An Unexplored Phytomedicine - Shahana Sharmin, Md. Tanvir Kabir, Md. Nasiful Islam, Mohd. Raeed Jamiruddin, Imon Rahman, Arifur Rahman, Mahboob Hossain (Journal of Applied Pharmaceutical Science, 2018)
Aporosa wallichii Hook.f. is a medicinal plant, which belongs to Phyllanthaceae family. This plant was used in this study for the determination of several pharmacological activities. This study involved experiments including determination of antioxidant property by performing 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay and total phenolic content (TPC) test, determination of cytotoxic activity by brine shrimp lethality assay and thrombolytic property analysis. In this study, it was observed that for DPPH free radical scavenging assay; standard (ascorbic acid) provided the IC50 value of 75.6 μg/mL, whereas the extract provided the IC50 value of 58.7 μg/mL. In case of TPC test, plant extract showed 308.97 mg of gallic acid equivalents/g of extract. Brine shrimp lethality bioassay revealed the cytotoxic property of the plant and the LC50 value of the plant extract was 26.7 μg/mL. Then again, the standard vincristine sulfate provided the LC50 value of 2.0 μg/mL. Moreover, the thrombolytic analysis showed for standard (clopidogrel) 59.3% clot lysis and for extract 24.5 % clot lysis. This study revealed that this plant has significant antioxidant activity, moderate level of cytotoxic activity and thrombolytic activity.
Keywords: DPPH free radical scavenging assay, Total phenolic content, Brine shrimp lethality assay, Thrombolytic property, Cytotoxicity.